UPAYA PENINGKATAN HASIL BELAJAR SISWA KONSEP SHOOTING BOLA BASKET MELALUI MODIFIKASI SARANA PEMBELAJARAN - Syahnuar Syahnuar (Jurnal Muara Pendidikan, 2020)
Modified basketball sport will be able to develop children’s skills faster than standard equipment for adults because they are not obstructed by equipment that is too heavy and the field is too broad according to the child, and finally that modified sport can foster joy and pleasure in children. Children in competitive situations by modifying learning by modifying learning tools.The use of aids in the form of modification of basketball learning facilities in the implementation of this research is an alternative that can be used by the teacher to draw student’s attention in learning. Before the implementation of the action, students who succeeded in completing the minimum score of 75 for learning outcomes in shooting basketball were 5 students out of 26 students or about 19,23%.Futhermore, it experienced an increase after taking action, namely the learning outcomes of shooting basketball increased to 96,2% or about 25 students. So that the quality of the learning process on the ability to perform basic motion shooting basketball that can be seen student leaning outcomnes that have been improved that has been done in class IX A Junior High School 1 Muaro Jambi district Muaro Jambi in an effort to improve learning outcomes in basketball shooting by implementing modification of learning fasilities managed to improve learning outcomes in basket ball shooting.